Udžbenik filozofije pozitivnog prava / A Significant Contribution to the Study of Law - Hodžić, Dželaludin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
This text is the review of a book by Riccardo Guastini Syntax of Law (Zagreb, Naklada Breza, 2016, pg.415) translated by Luka Burazin.